Integrating Cold Thermal Energy Storage for Air Conditioning Demand in a CO2 Refrigeration System at a Supermarket - Davide Tommasini; Håkon Selvnes; Armin Hafner (Energies)
A common configuration for transcritical CO2 booster systems in supermarkets involves air conditioning (AC) supplied by cooling a water-glycol circuit. The design capacity of the refrigeration unit must handle all refrigeration loads and the AC load during the hottest summer day, leading to overcapacity and part-load operation for most of the year. A proposed design for implementing cold thermal energy storage (CTES) dedicated to AC demand in a supermarket located in the Oslo region is modeled in the object-oriented language Modelica. Simulation results demonstrate an electricity peak power reduction of up to 32.33%. Even though energy savings are not the primary objective of this project, they are achieved by producing and storing energy when the outdoor temperature is lower, and the coefficient of performance (COP) of the system is higher. The energy savings can reach up to 11.8%. Finally, the economic benefits of the system are assessed under the spot pricing system, revealing potential electricity cost savings of up to 12.56%.